Tenable: How lucrative are vulnerabilities?. Issue 12 (December 2019) - Unknown
Abstract : One of the take-away messages from this report, sub-titled 'A closer look at the economics of the exploit supply chain' is that cyber criminals are earning around 12 times as much as organisations are spending on cyber security. Gartner estimates that the cyber security spend worldwide will amount to around 136bn in 2019. But the bad guys are pumping 200bn just through money laundering operations alone.